2017
DOI: 10.7554/elife.20882
|View full text |Cite|
|
Sign up to set email alerts
|

Constitutive scaffolding of multiple Wnt enhanceosome components by Legless/BCL9

Abstract: Wnt/β-catenin signaling elicits context-dependent transcription switches that determine normal development and oncogenesis. These are mediated by the Wnt enhanceosome, a multiprotein complex binding to the Pygo chromatin reader and acting through TCF/LEF-responsive enhancers. Pygo renders this complex Wnt-responsive, by capturing β-catenin via the Legless/BCL9 adaptor. We used CRISPR/Cas9 genome engineering of Drosophila legless (lgs) and human BCL9 and B9L to show that the C-terminus downstream of their adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 75 publications
3
91
0
Order By: Relevance
“…Other studies have identified additional regulatory complexes, such as the DOTCOM complex, that contribute to β‐catenin regulation of transcription (Mohan et al, ), but complexes such as these are more broadly acting and are not necessarily dedicated to β‐catenin‐TCF/LEF complexes (Cadigan and Waterman, ). More recently, there have been exciting advances in identifying the specific complex of proteins established by TCF/LEFs on chromatin and understanding how that complex is modified by Wnt signalling and β‐catenin (Chodaparambil et al, ; Fiedler et al, ; van Tienen et al, ) (Figure ). The old model of β‐catenin displacing Groucho/TLE repressors from TCF/LEFs to activate gene expression clearly needs refinement as current studies suggest that co‐repressors and co‐activators might exist simultaneously.…”
Section: Compounds Targeting Wnt Co‐factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have identified additional regulatory complexes, such as the DOTCOM complex, that contribute to β‐catenin regulation of transcription (Mohan et al, ), but complexes such as these are more broadly acting and are not necessarily dedicated to β‐catenin‐TCF/LEF complexes (Cadigan and Waterman, ). More recently, there have been exciting advances in identifying the specific complex of proteins established by TCF/LEFs on chromatin and understanding how that complex is modified by Wnt signalling and β‐catenin (Chodaparambil et al, ; Fiedler et al, ; van Tienen et al, ) (Figure ). The old model of β‐catenin displacing Groucho/TLE repressors from TCF/LEFs to activate gene expression clearly needs refinement as current studies suggest that co‐repressors and co‐activators might exist simultaneously.…”
Section: Compounds Targeting Wnt Co‐factorsmentioning
confidence: 99%
“…As discussed at the beginning of this section, the TCF/LEF–β‐catenin transcriptional complex has been found to be tightly regulated in a context‐dependent manner by different co‐regulatory factors that assemble at WREs in promoters and enhancers of target genes (Figure ) (Levanon et al, ; Waltzer and Bienz, ; Hecht et al, ; Sun et al, ; Takemaru and Moon, ; Brantjes et al, ; Chodaparambil et al, ; Fiedler et al, ; van Tienen et al, ). These findings have led to a ‘Wnt enhanceosome model’ (Fiedler et al, ).…”
Section: Compounds Targeting Wnt Co‐factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A) As described by Franz et al, many Wnt target genes show no evidence of TCF/Pan dependent repression in the absence of Wnt signaling. B) Model proposed in van Tienen et al, where in the absence of Wnt signaling, TLE, BCL9/B9L, and Pygo proteins co‐occupy W‐CRMs. C) This model postulated that these factors are also associated with TCF in Wnt‐stimulated cells, along with β‐catenin and other co‐activators.…”
Section: Is the Transcriptional Switch A General Feature Of Wnt Genementioning
confidence: 99%
“…Interestingly, Pygo also associates with Gro in flies, and analysis of gro , pygo double mutants suggests that a major function of Pygo is to inactivate Gro . A recent study examined proteins associated with biotin ligase‐tagged BCL9 and B9L, in the presence and absence of Wnt signaling using a technique called BioID. Surprisingly, the authors found both BCL9 and B9L associated with TLEs irrespective of the state of Wnt signaling in HEK293 cells.…”
Section: Does Activation Of Wnt Signaling Lead To Displacement Of Tlementioning
confidence: 99%